Communicative Language Teaching Through Role-Play: Effects on Indonesian EFL Students’ Speaking Ability - winarno, winarno; Ramli; Fitriawati; Cahyo Budi Sampurno (LETS: Journal of Linguistics and English Teaching Studies, 2026)
Speaking remains a challenging skill for many Indonesian EFL learners, particularly when classroom instruction provides limited opportunities for sustained oral interaction. Although role-play has been widely associated with Communicative Language Teaching (CLT), further classroom-based evidence is still needed from ordinary public secondary school contexts, especially when students’ post-treatment performance is assessed through a task different from the practiced role-play format. This study examined whether role-play implemented within a CLT framework improved the speaking ability of eleventh-grade students at SMAN 1 Tarakan. A pre-experimental one-group pre-test and post-test design was employed involving one intact class. Thirty students who completed both tests were included in the final analysis. Students’ speaking performance was assessed using Brown’s (2004) analytical rubric, covering pronunciation, grammar, vocabulary, fluency, and comprehension. The intervention consisted of four structured role-play sessions that progressed from guided practice to more independent performance. The results showed that students’ mean score increased from 43.47 in the pre-test to 76.13 in the post-test. Since the post-test scores were not normally distributed, the Wilcoxon signed-rank test was applied. The result indicated a statistically significant difference between the pre-test and post-test scores (Z = -4.802, p < .001), with a large effect size (r = .88). Classroom observation also showed gradual improvement in students’ participation, confidence, interaction, pronunciation, and readiness to communicate. These findings suggest that role-play can support speaking development by providing meaningful situations, repeated rehearsal, peer interaction, and constructive feedback.